Trypsin Activates Human Platelets via Proteolytic Cleavage of Protease-activated Receptor 4 (PAR4) - Webb, Emma M.; Seymour, Kendal; Hamm, Heidi (Thrombosis and Haemostasis)
Human platelets express protease activated receptor (PAR) 1 and 4 on the platelet membrane. PAR1 activation is crucial for hemostasis, while PAR4 activation produces a prolonged pro-inflammatory platelet response. Once activated, the PAR receptors cause platelet activation and aggregation. The PARs are activated by proteolytic cleavage of their N-terminus, revealing a new N-terminus dubbed the tethered ligand. The tethered ligand folds back and activates the receptor. PAR1 and PAR4 differ in their tethered ligand sequence, as well as their signaling cascades, however, they are both activated by various serine proteases, specifically thrombin. Much is known about PAR4 activation via thrombin cleavage, however, little is known about activation by other proteases. Thrombin cleavage of PAR4 and subsequent activation leads to G proteins, Gαq and Gα12/13, and β-arrestin signaling. Here, we have demonstrated trypsin activates human platelets solely though PAR4. Trypsin activated PAR4 signals through both Gαq and Gα12/13 as effectively as thrombin. Thrombin may be the main protease to activate PAR4 under typical conditions, however under pathological conditions, such as acute pancreatitis (AP), trypsin activation of PAR4 may be a main driver of platelet activation and disease progression.